THE QVINQVATRVS OF JUNE, MARSYAS AND LIBERTAS IN THE LATE ROMAN REPUBLIC. (2nd May 2018) - López Barja De Quiroga, Pedro
Abstract : Masked revelry, the quaffing of large amounts of wine and the sound of flutes … this cavalcade would pass through the streets of Rome every 13th June, even crossing the forum itself. As we will show later on, a connection can be established between this celebration (the Quinquatrus minusculae ) and the statue of Marsyas, the acolyte of Dionysus, which stood in the forum and was associated with freedom, wine and charivari. In turn, this connection will open the way for a new interpretation of the multiple meanings of the feast and the satyr in the highly charged political atmosphere of Late Republican Rome. The main aim of this study will be to show, in the third part of this article, how populares politicians tried to exploit the opportunities presented to them by religious festivities and ludi to draw more of the public into their contiones or to obtain a favourable verdict in a political trial.